2022
DOI: 10.1155/2022/3116303
|View full text |Cite|
|
Sign up to set email alerts
|

MCM6 Promotes Hepatocellular Carcinoma Progression via the Notch Pathway: Clinical, Functional, and Genomic Insights

Abstract: Objective. To evaluate the expression profile of MCM6 in HCC and the relationship between MCM6 level and clinicopathological parameters through bioinformatics analysis of several databases. Methods. MCM expression level, clinical parameters, survival data, and gene set enrichment analysis were analyzed by bioinformatics database, including Oncomine™, UALCAN, HCCDB, TCGA, cBioPortal, and LinkedOmics. Real-time PCR, western blotting, and IHC staining were conducted to identify the expression of MCM6 in HCC compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the contrary, WGCNA combining with TCGA and GEO analysis identified that exceptional expression of MCM6 reflects pathologic stage of multiple tumors, serving as putative biomarkers for breast cancer, 285–287 gastric cancer, 288,289 renal cell carcinoma, 215,290,291 HCC, 292–295 and non‐small cell lung carcinoma 217,296,297 . Meanwhile, MCM7 is widely regarded as an extensive biomarker in multiple tumor types since its overexpression pattern 233,234,298–310 .…”
Section: Dna Replication Disease and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, WGCNA combining with TCGA and GEO analysis identified that exceptional expression of MCM6 reflects pathologic stage of multiple tumors, serving as putative biomarkers for breast cancer, 285–287 gastric cancer, 288,289 renal cell carcinoma, 215,290,291 HCC, 292–295 and non‐small cell lung carcinoma 217,296,297 . Meanwhile, MCM7 is widely regarded as an extensive biomarker in multiple tumor types since its overexpression pattern 233,234,298–310 .…”
Section: Dna Replication Disease and Therapymentioning
confidence: 99%
“…115,225,[273][274][275] Consistent with this notion, overexpression of MCM5 also associates with tumor stages, which appears to be potential diagnostic and prognostic markers in thyroid cancer, 276,277 ovarian cancer, 269,[278][279][280] bladder cancer, [281][282][283] and renal cell carcinoma. 284 On the contrary, WGCNA combining with TCGA and GEO analysis identified that exceptional expression of MCM6 reflects pathologic stage of multiple tumors, serving as putative biomarkers for breast cancer, [285][286][287] gastric cancer, 288,289 renal cell carcinoma, 215,290,291 HCC, [292][293][294][295] and non-small cell lung carcinoma. 217,296,297 Meanwhile, MCM7 is widely regarded as an extensive biomarker in multiple tumor types since its overexpression pattern.…”
Section: Mcms As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%